2006
DOI: 10.1016/j.cardiores.2005.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and peripheral actions of growth hormone and its releasing peptides: Relevance for the treatment of cardiomyopathies

Abstract: Ischemic and nonischemic cardiomyopathies are associated with significant morbidity and mortality in industrialized countries. Cardiomyopathies of primary origin, and more specifically the dilated form of the disease, have been associated with a number of gene defects in cytoskeletal, membrane, and sarcomeric proteins. Cardiomyopathies of secondary origin such as ischemic cardiomyopathy remain the leading cause of left ventricular systolic dysfunction and heart failure. Among novel strategies to improve cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 94 publications
2
30
0
Order By: Relevance
“…Importantly, all treatments with recombinant human GH in rats had a clear limitation, due perhaps to the production of anti-GH antibodies after 2 weeks of treatment (23). Therefore, the long-term effects (either beneficial or deleterious) remain unknown in these models (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, all treatments with recombinant human GH in rats had a clear limitation, due perhaps to the production of anti-GH antibodies after 2 weeks of treatment (23). Therefore, the long-term effects (either beneficial or deleterious) remain unknown in these models (8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to GH itself and IGF-1, GH-releasing peptides such as ghrelin and synthetic GH secretagogues (GHS) are also suggested to have cardiac effects (5)(6)(7)(8), and growth hormone-releasing hormone (GHRH) mRNA is detected in peripheral tissues, including the heart (9, 10), consistent with widespread biologic signaling potential beyond the hypothalamic-pituitary axis.…”
mentioning
confidence: 99%
“…Studies of rhIGF-I use in heart failure in humans have shown no beneficial effect 60. Studies are ongoing of cardiovascular risk factors comparing the effects of rhGH and rhIGF-I.…”
mentioning
confidence: 98%
“…9,13,14 Human growth hormone has also been shown to improve cardiac function in patients with chronic heart failure. 15 We have been interested in TGFb 1 since this growth factor is abundant in platelets, which can limit ischemic injury to the heart. 9 In previous studies, TGFb 1 was shown to reduce apoptosis and necrosis in cultured rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%